QRS voltage in precordial leads in patients with neurally mediated syncope. (25th November 2020) - Blendea, D; Cimpeanu, M; Jelnean, M; Chiorescu, R; Crisan, S; Pop, S
Abstract: Background: We have previously demonstrated that patients with neurally mediated syncope (NMS) who have an isolated QRS complex, of very low voltage (≤0.3mV cutoff), in one of the frontal leads on the 12-lead electrocardiogram have a threefold increase in the risk of syncope recurrence. The potential relationship between isolated low voltage (ILV) in precordial leads (Figure A) and recurrent NMS has not been yet explored. Purpose: To prospectively evaluate whether the presence of ILV in the precordial leads predicts recurrence of NMS. Methods: We included 135 patients with NMS (age 49±20) years, with a median of 4 syncopal episodes. During a median period of 15 months, 43 patients (32%) experienced recurrent syncope. The lowest QRS voltage (QRSmin) was determined separately for the frontal and precordial leads. The cutoff for precordial QRSmin that best discriminated between patients with recurrent and no recurrent syncope was ≤0.7mV (ROC curve AUC=0.65). Results: Isolated low voltage in precordial leads was present in 49 (36%) of patients. The lead which displayed QRSmin in the precordial leads was V1 in 35 (71%) patients. The actuarial total syncope recurrence rate at 1 year was 26% (95% CI 16–42%) in patients with ILV in precordial leads, and 21% (95% CI 6–39%) in patients without ILV (log rank test P=0.043; Figure B). The significant relationship between the presence of ILV in precordial leads and syncope recurrence was retained in Cox multivariate analysis that included isolated very low voltage in frontal leads (≤0.3mV cutoff), as well as the number of syncopal episodes. Conclusions: Isolated low QRS voltage in the precordial leads predicts recurrence of NMS independent of isolated low QRS voltage in the frontal leads. Funding Acknowledgement: Type of funding source: None